Localization and patterns of Cerebral dyschromatopsia: A study of subjects with prospagnosia. (August 2016) - Moroz, Daniel; Corrow, Sherryse L.; Corrow, Jeffrey C.; Barton, Alistair R.S.; Duchaine, Brad; Barton, Jason J.S.
Abstract: Objective: Cerebral dyschromatopsia is sometimes associated with acquired prosopagnosia. Given the variability in structural lesions that cause acquired prosopagnosia, this study aimed to investigate the structural correlates of prosopagnosia-associated dyschromatopsia, and to determine if such colour processing deficits could also accompany developmental prosopagnosia. In addition, we studied whether cerebral dyschromatopsia is typified by a consistent pattern of hue impairments. Methods: We investigated hue discrimination in a cohort of 12 subjects with acquired prosopagnosia and 9 with developmental prosopagnosia, along with 42 matched controls, using the Farnsworth-Munsell 100-hue test. Results: We found impaired hue discrimination in six subjects with acquired prosopagnosia, five with bilateral and one with a unilateral occipitotemporal lesion. Structural MRI analysis showed maximum overlap of lesions in the right and left lingual and fusiform gyri. Fourier analysis of their error scores showed tritanopic-like deficits and blue-green impairments, similar to tendencies displayed by the healthy controls. Three subjects also showed a novel fourth Fourier component, indicating additional peak deficits in purple and green-yellow regions. No subject with developmental prosopagnosia had impaired hue discrimination. Conclusions: In our subjects with prosopagnosia, dyschromatopsia occurred in those with acquired lesions of the fusiform gyri, usually bilateral but sometimes unilateral. The dyschromatopsic deficit shows mainly an accentuation of normal tritatanopic-like tendencies. These are sometimes accompanied by additional deficits, although these could represent artifacts of the testing procedure. Highlights: We investigated hue discrimination in acquired and developmental prosopagnosia. Lesions to the fusiform gyri but not anterior temporal cortex caused dyschromatopsia. Developmental prosopagnosia is not associated with impaired hue discrimination. Cerebral dyschromatopsia is mainly an accentuation of normal tritanopic-like tendencies.